KERAGAMAN JAMUR MAKROSKOPIS DI TAMAN HUTAN RAYA SULTAN ADAM MANDIANGIN KALIMANTAN SELATAN - Rahmi, Fatimah; Ajizah, Aulia; Amintarti, Sri (BIOEDUKASI (Jurnal Pendidikan Biologi), 2024)
The Sultan Adam Mandiangin Grand Forest Park has a high biodiversity with a variety of plants. This study aims to describe the types of macroscopic fungal found in the Sultan Adam Mandiangin Grand Forest Park area. The data were obtained using the total roaming method, and then the morphological characteristics of each sample of macroscopic fungal were found. Data analysis was carried out by identifying species concerning the literature. The results of the study found 18 species of macroscopic fungi, belonging to 7 families, namely: Marasmius elegans, Marasmius sp.1, Marasmius sp.2, Polyporus alveolaris, Neofavolus alveolaris, Polyporus sp., Trametes hirsuta, Trametes gibbosa, Trametes sp., Fomes sp., Lycoperdon sp., Lycoperdon pyriforme, Irpex lacteus, Thelephora terrestris, Ganoderma sp.1, Ganoderma sp.2, Daldinia sp., dan Daldinia concentrica.  The results of this study are expected to provide information about the biodiversity of macroscopic fungi in South Kalimantan.